2020
DOI: 10.1016/j.joi.2020.101072
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge spillovers: Does the geographic proximity effect decay over time? A discipline-level analysis, accounting for cognitive proximity, with and without self-citations

Abstract: This work analyzes the variation over time of the effect of geographic distance on knowledge flows. The flows are measured through the citations exchanged between scientific publications, including and excluding self-citations. To calculate geographic distances between citing and cited publication, each publication is associated with a "prevailing" territory, according to the authors' affiliations. We then apply a gravity model to account for the research size of the territories, in terms of cognitive proximit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This finding opens to question the consolidated thesis of the geographical proximity of knowledge spillovers, previously demonstrated through the analysis of patent citations (Jaffe, Trajtenberg, & Henderson, 1993): unlike technical knowledge encoded in patents, scientific knowledge appears to flow rather easily across national borders. Further analyses carried out by the authors (Abramo, D'Angelo, & Di Costa, 2020b) reveal that in domestic knowledge flows, geographic proximity remains an influential factor, although with differences among disciplines and decaying along time. At the same time, the effect of distance on continental flows is modest, and negligible on intercontinental flows.…”
Section: Discussionmentioning
confidence: 94%
“…This finding opens to question the consolidated thesis of the geographical proximity of knowledge spillovers, previously demonstrated through the analysis of patent citations (Jaffe, Trajtenberg, & Henderson, 1993): unlike technical knowledge encoded in patents, scientific knowledge appears to flow rather easily across national borders. Further analyses carried out by the authors (Abramo, D'Angelo, & Di Costa, 2020b) reveal that in domestic knowledge flows, geographic proximity remains an influential factor, although with differences among disciplines and decaying along time. At the same time, the effect of distance on continental flows is modest, and negligible on intercontinental flows.…”
Section: Discussionmentioning
confidence: 94%
“…Analyzing and predicting important publications, citations, and author cocitations have been an active area of research (Savov et al, 2020;Bu et al, 2020). Citation of research publications is an indicator of how scientific knowledge spreads (Abramo et al, 2020;Liang et al, 2020). Stegehuis et al (2015) proposed quantile-based regression models to predict future citations.…”
Section: Citation As Impact Indicatormentioning
confidence: 99%
“…Lee et al (2020) took different types of subsidiaries in multinational companies as the research object and found that the governance type of subsidiaries affects the flow of knowledge within multinational companies. Abramo et al (2020aAbramo et al ( , 2020b concluded through an analysis of patent data that geographic distance has a significant impact on the flow of knowledge at the national level but is irrelevant at the intercontinental level. On this basis, Abramo et al (2020aAbramo et al ( , 2020b introduced time and found that as time passes, the influence of geographic distance on the flow of knowledge gradually weakens.…”
Section: Introductionmentioning
confidence: 99%